Uterine Didelphys with Obstructed Left Hemivagina with Haematometrocolpos: A Rare Congenital Cause of Lower Abdominal Pain in Young Female - Sandhu, Gurpreet Singh; Singh, Aruna; Singh, Lokesh (Archives of Clinical and Medical Case Reports, 2020)
Uterus didelphys is a very rare mullerian duct anomaly and is part of various congenital anomalies of female genital tract. We report a case of eighteen years old female presenting with lower abdominal pain and dysmenorrhorea diagnosed to have uterine didelphys with obstructed left hemivagina with haematometrocolpos on MRI and managed by excision of vaginal septum and relieved of symptoms. <gdiv></gdiv>